Teacher Self-Evaluation Models As Authentic Portfolio To Monitor Language Teachers Performance - Singgih Widodo (TEFLIN Journal: A publication on the teaching and learning of English, 2004)
Many principals or heads of English departments usually use supervising checklists to monitor or evaluate their teachers performance. As a matter of fact, teachers may not feel satisfied with the feedback they have got from their superiors. This paper aims at inspiring them with ideas of self-learning to improve their own teaching performance for professional development. In this paper, the writer would like to share his own experience as a principal and a head of the English department by exploring self-evaluation models to monitor language teachers performance in the classroom. For this purpose, it is necessary to identify the needs of language teachers and later this teacher portfolio may also help principals or head of the department evaluate their teachers performance.